Pepstatina, um inibidor da pepsina, protege as alterações inflamatórias e funcionais pulmonares secundária ao refluxo gastroesofágico em camundongos - Sales, Thiago Meneses Araújo Leite (2022)
Gastroesophageal reflux disease (GERD) is prevalent and associated with esophageal and extraesophageal syndromes, which include various pulmonary conditions. GERD can lead to pulmonary complications through the mechanisms of microaspiration or spasm of the airways mediated by the vagal nerve. In this sense, antireflux surgery improves the results of some pulmonary complications of GERD, however there is no effective and/or less invasive drug therapy to treat this condition secondary to reflux. Objective: In the present study, we aimed to evaluate the effect of pepstatin, a pepsin inhibitor, in the protection of pulmonary inflammatory and functional alterations secondary to gastroesophageal reflux in mice. Materials and Methods: The surgical model of reflux consists of pyloric substenosis and gastric fundus ligation in swiss mice. First, a time course was performed to define the day with the highest lung inflammation. The experimental groups were: sham (sham operated) was the control, experimental GERD 7 days, experimental GERD 21 days and experimental GERD 28 days after surgery. At the end of these days, the animals were euthanized and the lungs were removed for measurement of wet weight (PU), Myeloperoxide (MPO) activity, histological damage (alveolitis and fibrosis), cytokines IL-6, KC and IL-10, concentrations of glutathione (GSH), malondialdehyde (MDA) levels, nitric oxide, through the nitrate/nitrite ratio (NO3/NO2) and hydroxyproline content. In addition, lung function was assessed by spirometry (expiratory flow [EF] and volume per minute [MV]) and finally tracheal contractility (KCL and CCH). In other experimental groups, the animals were treated daily with pepstatin (pepsin inhibitor, 0.3 mg/kg via gavage), omperazol (proton pump inhibitor, 40mg/kg via intraperitoneally) or saline solution (control). At the end of 28 days, the animals were euthanized and the same parameters were evaluated. Results: It was observed that the GERD 28 days group had a significant increase (P < 0.05) in PU and MPO when compared to the sham and the GERD 21 days group. From these results the model on the 28th day was selected for the following experiments. When checking the histopathological damage (alveolitis and fibrosis), cytokines IL-6, KC and IL-10, GSH, MDA and NO3/NO2 and hydroxyproline content, it was observed that the GERD 28 days group showed significant differences (P < 0, 05) when compared to sham. Regarding pulmonary function, it was seen that in animals of the GERD group 28 days had a significant decrease (P < 0.05) in EF and MV, when compared to animals of the sham group. Regarding tracheal contractility, it was observed in the GERD group 28 days showed greater reactivity (P < 0.05), both by KCl and by CCH when compared to the sham group. Pepsin inhibition partially protected the lung against inflammatory changes, pro-oxidant and fibrotic activity, lung function and tracheal contractility, when compared to the GERD group at 28 days. Conclusion: Experimental gastroesophageal reflux in mice induced secondary inflammation, pro-oxidant, fibrotic activity, lung dysfunction, contractility and inhibition of pepsin activity was able to partially protect the lung against reflux.